Penolakan Undang-Undang Cipta Kerja Omnibus Law pada Klaster Ketenagakerjaan - Naufal, Tondy; Ibadurrahman, Yasin; Fadhilah, Faiz Nur Aziz (Kopertais Wilayah I DKI Jakarta dan Banten, 2023)
This study aims to analyze the rejection of the Omnibus Law on Job Creation, especially in the employment cluster. The focus of the study is to understand the reasons behind the rejection, as well as the social, economic, and political impacts that arise as a result of the rejection. This study uses a qualitative approach with a case study design. Primary data were collected through a questionnaire specifically designed to explore various aspects of online shopping behavior. This questionnaire helps gain insight into consumer interactions with digital platforms and the factors that influence their decisions. This case study provides an in-depth understanding of the reasons and impacts of rejection of the employment cluster in the Job Creation Law. The results of the study show that rejection of the Omnibus Law on the employment cluster was driven by several main reasons, including concerns about the weakening of workers' rights, such as the right to leave, severance pay, and minimum wages. The Job Creation Law is also considered to make it easier for companies to carry out Termination of Employment (PHK) and reduce social security, which makes workers more vulnerable. In addition, the process of discussing the law, which was considered less transparent and did not involve adequate public participation, raised suspicions that this law benefits employers more than workers. Rejection of the Job Creation Law has sparked various forms of protest, including street demonstrations, strikes, and online campaigns. The impact of this rejection includes legal and political instability, which affects foreign investor confidence and economic growth. Conflicts of interest between the government, employers, and workers complicate the situation, and the resulting uncertainty can disrupt industrial relations and economic growth.